Do Computer and Foreign language literacy affect native language (L1) reading strategies? - Mavrogianni, Aristea; Vassilaki Εleni; Sarris, Apostolos; Yachnakis, Emmanuel (Advances in Social Sciences Research Journal, 2021)
This research investigates metacognitive awareness, students reading strategies preferences and their correlation to independent demographic and educational variables. Data were gathered through the MARSI-2fGR inventory administered to a random sample of 632 students aged 12-24 from 68 schools in various urban, semi-urban and rural regions in Greece. The alternative factorial structure of the MARSI-2fGR inventory comprised of two factors, namely textor and textout, standing for text-oriented and beyond text reading strategies that Greek secondary students use. Results showed significant differences in favour of the textor reading strategies compared to the textout. It seems that other parameters affect the reading strategies preferences more than the family’s socioeconomic status. Both variables of foreign language knowledge and computer literacy showed statistically significant differences. Therefore, it appeared that the more literate someone is in foreign languages and computers, the more reading strategies he/she declared to use. This research sheds new light on the way that Greek students read academic or school-related material.